Knowledge and awareness of dentists on child abuse and neglect in Türkiye - Aslı Aşık; Ece Eden (Arbu Academic Publishing, 2022)
Aim: Child abuse and neglect (CAN) may be defined as physical, sexual and/or psychological maltreatment of the child. The purpose of this paper was to evaluate the knowledge and awareness of dentists about CAN, to give basic information on the topic and to take feedback. Methods: It was an observational study that the questionnaire that consisted 26 questions in four parts was sent by e-mail with an electronic link via Turkish Dental Association to Turkish dentists. At the end of the questionnaire, a short education by power-point presentation was given to volunteered participants and self-competence feedbacks were taken. Results: A total of 326 dentists (113 males and 213 females) aged 23-70 years, answered the questionnaire. Only 16.2% of dentists reported that they know their legal rights and information on reporting CAN. 79.5% of dentists noted that they did not receive education on CAN during their undergraduate years. 95.6% of the participants volunteered to attend the education provided. Feedbacks showed that information obtained by the education had a beneficial impact on dentists' awareness and knowledge. Conclusions: Turkish dentists' knowledge and awareness of CAN were inadequate. Educational efforts may enable them to recognize cultural misperceptions, take necessary precautions, to be confident in reporting child abuse and neglect without hesitation and fulfill their legal obligations.